Pengembangan Modul Ikatan Kimia dan Bentuk Molekul Berorientasi Nature of Science Untuk Menumbuhkan Literasi Sains Siswa - Nurwanti, Hifzani; Khery, Yusran; Nufida, Baiq Asma (IKIP Mataram, 2018)
This development aims to determine the characteristics and feasibility of the oNature of Science (NOS) oriented module On the Chemical Bonds andMolecular Forms subject material through the 4D stage (Define, design,develop and disseminate). This research and development is carried out up tothe stage of development (development) with adjustments based ondevelopment needs. The module prototype was validated by 2 expertvalidator, 1 practitioner validator and 10 students as limited test respondents.Quantitative data were analyzed by percentage formulas and category.Qualitative data in the form of responses and suggestions are used asconsiderations for revisions. The results of expert validation showed anaverage percentage of 92.67% with very good categories of material experts,83.34% with very good categories from product design experts and 76% withgood categories from teacher practitioners. The average response of studentsto the modul prototype is 85.1% with a very good category. This shows thatthe module that developed is feasible to proceed to a large-scale trial phase.